Prenatal diagnosis of partial monosomy 8p (8p23.2→pter) and partial trisomy 15q (15q21.2→qter) and incidental detection of a familial chromosome translocation of paternal origin in a pregnancy associated with increased nuchal translucency and an abnormal maternal serum screening result - Chih-Ping Chen; Tsang-Ming Ko; Liang-Kai Wang; Schu-Rern Chern; Peih-Shan Wu; Shin-Wen Chen; Fang-Tzu Wu; Li-Feng Chen; Wayseen Wang (Elsevier, 2021)
Objective: We present partial monosomy 8p (8p23.2→pter) and partial trisomy 15q (15q21.2→qter) and incidental detection of a familial chromosome translocation of paternal origin in a pregnancy associated with increased nuchal translucency (NT) and an abnormal maternal serum screening result. Case Report: A 29-year-old primigravid woman underwent chorionic villus sampling (CVS) at 13 weeks of gestation because of an increased NT thickness of 3.2 mm at 12 weeks of gestation and an abnormal maternal serum screening for Down syndrome result with a calculated risk of 1/29. Her husband was 33 years old, and there was no family history of congenital malformations. CVS revealed a derived chromosome 8 or der(8). Cytogenetic analysis of the parents revealed a karyotype of 46,XY,t(8;15)(p21.3;q13) in the father and a karyotype of 46,XX in the mother. The CVS result was 46,XY,der(8)t(8;15)(p21.3;q13)pat. The woman requested for amniocentesis at 16 weeks of gestation. Array comparative genomic hybridization (aCGH) analysis on the DNA extracted from uncultured amniocytes revealed a result of arr 8p23.3p23.2 (191,530-2,625,470) × 1.0, arr 15q21.2q26.3 (50,903,432-102,338,129) × 3.0 with a 2.434-Mb deletion of 8p23.3-p23.2 including DLGAP2, CLN8 and ARHGEF10, and a 51.435-Mb duplication of 15q21.2-q26.3 including CYP19A1 and IGF1R. Conventional cytogenetic analysis of cultured amniocytes revealed the result of 46,XY,der(8) t(8;15)(p23.2;q21.2)pat in the fetus. The pregnancy was subsequently terminated, and a malformed fetus was delivered with characteristic craniofacial dysmorphism. Conclusion: Maternal serum screening and NT screening may incidentally detect familial unbalanced reciprocal translocations, and aCGH analysis is useful for a precise determination of the breakpoints of the translocation and the involvement of the related genes under such a circumstance.